Влияние плотной низкотемпературной плазмы на измерения индуктивными петлями; Известия вузов. Физика; Т. 58, № 9-2 - Русских А. Г. Александр Геннадьевич; Жигалин А. С. Александр Сергеевич; Орешкин В. И. Владимир Иванович; Митрофанов К. Н. Константин Николаевич (2015, 2015)
Заглавие с экрана